Extent of Information Utilization Behaviour of Vegetable Growers Regarding Integrated Pest Management Practices - Narendra Kumar Choudhary,; Rajendra Rathore, Manoj Kumar Sharma, Jitendra Kumar, Rajesh Kumar Serawat, Meenakshi Jakhar, (Indian Journal of Extension Education, 2022)
The study was undertaken in the Jaipur district of Rajasthan. Chomu and Amber tehsil were selected for the research purpose as Chomu and Amber have the maximum number of vegetable growers in the Jaipur district. List of villages in the selected tehsils were prepared, out of which, eight villages had the maximum number of vegetable growers from the two identified Tehsils. From each selected villages a sample of 15 respondents was selected randomly making a total of 120 respondents. It is evident from the study that the highest level of utilization was found in respect of the application of Cultural practices as summer ploughing followed by crop rotation. In Mechanical/ physical practices mass trapping of pests followed by use of pheromone traps was majorly utilized. Among Biological practices, use of predators followed by use of beneficial insects and among Chemical practices, uses of pesticides followed by safe application of pesticides were the major practices utilized.